Hepatitis E virus infection and its associated adverse feto-maternal outcomes among pregnant women in Qinhuangdao, China. (1st November 2020) - Li, Manyu; Bu, Qiuning; Gong, Wanyun; Li, Haomin; Wang, Lin; Li, Shuangshuang; Sridhar, Siddharth; CY Woo, Patrick; Wang, Ling
Abstract: Background and aims: The aim of this study was to investigate the positive rate of hepatitis E virus (HEV) infection and the possible adverse outcomes in pregnant women of Qinhuangdao, China. Methods: Serum samples of 946 pregnant women were collected from July 2017 to October 2017 in Qinhuangdao First Hospital. All samples were tested for anti-HEV IgM and IgG antibodies by enzyme-linked immunosorbent assay (ELISA). HEV RNA was tested by reverse transcription-nested polymerase chain reaction (RT-nPCR) and the PCR products were sequenced. Results: Of the 946 samples, the positive rate of anti-HEV IgM (15/365, 4.11%), anti-HEV IgG (74/365, 20.27%) and both anti-HEV IgM and IgG (12/365, 3.29%) were significantly higher ( p  < .05) in third trimester pregnant women than in the first (3/288, 1.04%; 36/288, 12.5%; 4/288, 1.39%), and second trimesters (6/293, 2.05%; 29/293, 9.90%; 2/293, 0.68%). The average alanine transaminase (ALT) level (34.49 ± 10.15) and the incidence of adverse pregnancy outcomes (13/18, 72.22%) in the both anti-HEV IgM and IgG positive group were significantly higher than other groups ( p  < .05). HEV RNA was detected in 1/181 (0.55%) of pregnant women with a history of HEV infection and the detected HEV strain belonged to subgenotype 4a. Conclusions: This study showed that pregnant women who have HEV infection can possibly lead to adverse pregnancy outcomes.